Nadiyah Marhani Siregar, Firman Eddy Design Of Childern’s Creativity Center In Medan City With Green Architecture Concept - Nadiyah Marhani Siregar; Firman Eddy (Talenta Publisher, 2024)
This journal is made for us to know how important a place is for our future kids to find knowledge easily.Therefore, the children who are still hesitant to know where to go can find the place convenient. The large number of children within Medan city for the availability of facilities that the development of children's creativity not directly proportional shows that this needs to be considered, especially since curious is a period of growth stimulation that can affect future growth and development. To resuscitate and tell other people how important for us to know, that future kids will suffer for knowledge. The main problem for them is the ignorance of themself to find out where they can find the receptacle to head to. Therefore, it is necessary to design facilities for a Children’s Creativity Centre in Medan City that can meet the needs of conditions and can accommodate recreational and educational activities for children that can affect children's development with a Green Architecture approach. This research uses qualitative descriptive methods through field information and literature studies. This building applies the Green Architecture concept in the form of saving energy, being way more flexible with climate, keeping it safe for the site, and respecting the people nearby. So that this design can be a forum for children's creativity, which is expected to respond to the condition of children both physically and psychically, which can improve children's creativity.